Mid-winter Scene in San Luis Obispo, Cal. [front and back] (1910)
A color view of a street with blooming flowers in San Luis Obispo. Text reads "Mrs. Brooks am with wth Mrs Warden here charged of the [Town?] Building. Ella J. [Yarmin?]"